Developing autonomous listening learning materials for university students TOEFL preparation - Sacko, Makan; Haidara, Youssouf (LingTera, 2018)
This research was aimed at developing autonomous listening learning materials for TOEFL preparation for learners at independent language learning center (ILLC) of the language development center at YSU to help them improve their listening skills. This research was a Research and Development study which refers to development model proposed by Tomlinson (1998). The subjects of this research were 30 learners who are members of ILLC. Data were collected using questionnaires and open-ended interviews. The data were analyzed qualitatively and quantitatively. The results of the research reveal that the appropriate listening learning materials for TOEFL preparation consist of printed materials and audio recording containing the listening skills to find the  main topic, to find the main idea, to find the implied meaning, to make prediction, to determine the meaning of idiomatic expressions, to find details information, to draw conclusions, to find suggestions, and to make inferences. The learners’ role is as active listeners and to answer  multiple choice questions, the learning activities include many listening practices, clear instructions, reflection and answer keys. Units are designed of Unit number/title, learning objectives, hints/tips, main activities and reflection. The appropriate tasks consist of warm-up, matching expressions to the pictures, matching words to their meanings, guessing, anticipating the topics and or questions, listening practices, note-taking.